1998
DOI: 10.1046/j.1365-2621.1998.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the force deformation curves of soaked red kidney beans (Phaseolus vulgaris L.)

Abstract: In this study, the textural patterns of red kidney beans soaked in water at 20, 30, 40 and 60 °C are reported. Texture (hardness) was measured instrumentally by cutting with a wedge‐type blade mounted on an Instron Universal Testing Machine at a speed of 200 mm min−1. The general trend of the force deformation curves was similar for all of the soaking temperatures studied throughout the soaking process. At initial stages of hydration, textural changes were a function of the soaking time. However, once the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
2
2
0
1
Order By: Relevance
“…Bourne (1967) has observed the large cavity in between the two cotyledons of red kidney beans, whereas other legumes have small cavity or no cavity at all. Similar observation was made by Abu‐Ghannam (1998) who studied the force deformation of soaked red kidney beans.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Bourne (1967) has observed the large cavity in between the two cotyledons of red kidney beans, whereas other legumes have small cavity or no cavity at all. Similar observation was made by Abu‐Ghannam (1998) who studied the force deformation of soaked red kidney beans.…”
Section: Resultssupporting
confidence: 82%
“…Although the study did not include textural measurements, it was expected that a hardening effect results from such a soaking treatment. Abu‐Ghannam (1998), in a study of texture of kidney beans during soaking, has observed that once the hydration process attained equilibrium, changes in texture became minimal, regardless of the soaking temperature and hydration time. Sefa‐Dedeh et al .…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to some level of plasticity attained by the seed coat during high-temperature cooking with water. A similar effect was observed for red kidney beans immersed in boiling distilled water at 100 • C for 1.5 min [28]. At stage C, the probe penetrates the seed coat and further compresses the bean.…”
Section: Bean Structure Deformation During Cookingsupporting
confidence: 72%
“…As soaking proceeds, water penetrates the seed coat, travelling through the cotedylons and towards the centre of the bean. Such water absorption causes the bean to become softer and uniform in texture (Abu-Ghannam, 1998a, 1998bDeshpande & Bal, 2001). Blanching is a common unit operation that affects the sensory characteristics of food.…”
Section: Introductionmentioning
confidence: 99%